Transcranial Direct Current Stimulation for Parkinson's Disease: A Systematic Review and Meta-Analysis - Liu, Xiang; Liu, Huiyu; Liu, Zicai; Rao, Jinzhu; Wang, Jing; Wang, Pu; Gong, Xiaoqian; Wen, Youliang (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is a common neurodegenerative disorder with motor and non-motor symptoms. Recently, as an adjuvant therapy, transcranial direct current stimulation (tDCS) has been shown to improve motor and non-motor function of PD. This systematic review aimed to evaluate the existing evidence of the efficacy of tDCS for PD. We included English databases (PubMed, the Cochrane Library, Embase, and Web of Science) and Chinese databases (Wanfang database, China National Knowledge Infrastructure [CNKI], China Science and Technology Journal Database [VIP], and China Biology Medicine [CBM]) without restricting the year of publication. Twenty-one tDCS studies, with a total of 736 participants, were included in the analysis. Two independent researchers extracted the data and characteristics of each study. There was a significant pooled effect size (-1.29; 95% CI = -1.60, -0.98; p<0.00001; I² = 0%) in the Unified Parkinson’s Disease Rating Scale I and the Montreal cognitive assessment (SMD=0.87, 95% CI = 0.50 to 1.24; p<0.00001; I² = 0%). A poor effect size was observed in the UPDRS III scores (SMD=-0.13; 95% CI = -0.64, 0.38; p=0.61; I² = 77%), and similar results were observed for the timed up and go test, Berg balance scale, and gait assessment. The results of this meta-analysis showed that there was insufficient evidence for tDCS to improve motor function of PD. However, tDCS seemed to improve cognitive performance. Further multicenter research with a larger sample size is needed. In addition, future research should focus on determining the tDCS parameters that are most beneficial to the functional recovery of patients with PD.